Magnetic and Thermoelectric Properties of Fe2CoGa Heusler Compounds - Tetsuji Saito; Hayai Watanabe (Inorganics)
The investigation of the properties of Heusler compounds is an important task that will pave the way for new applications in various fields related to magnetics and thermoelectrics. This study examines the magnetic and thermoelectric properties of Fe2CoGa Heusler compounds prepared by casting and subsequent annealing. The Fe2CoGa Heusler compound was found to be ferromagnetic, with a large saturation magnetization of 110 emu/g and a high Curie temperature of 1011 K. The Fe2CoGa Heusler compound was a good thermoelectric material, with a negative Seebeck coefficient of −44 μV/K, a low electrical resistivity of 0.60 μΩm, and a high-power factor of 3000 μW/mK2 at room temperature. The maximum power factor of 3230 μW/mK2 for the Fe2CoGa Heusler compound was obtained at 400 K. In order to improve the magnetic and thermoelectric properties of the Fe2CoGa Heusler compound, Fe2-xCo1+xGa (x = 0–1) Heusler compounds were also prepared by casting and subsequent annealing. In the Fe2-xCo1+xGa (x = 0–1) Heusler compounds, the saturation magnetization slightly decreased, but the Curie temperature increased with increasing Co content (x). As regards the thermoelectric properties, the electrical resistivity of the Fe2-xCo1+xGa (x = 0.25–1) Heusler compounds was smaller than that of the Fe2CoGa Heusler compound. The Seebeck coefficient and power factor of the Fe1.75Co1.25Ga Heusler compound were more significant than those of the Fe2CoGa Heusler compound. An increase in the Co content of the Fe2CoGa Heusler compound did not improve the saturation magnetization but improved the Curie temperature and thermoelectric properties of the Fe2CoGa Heusler compound. The Fe1.75Co1.25Ga Heusler compound exhibited a high-power factor value of over 4000 μW/mK2, which was comparable to that of the Bi2Te3 compound.